A perspective on heavy metal(loid)s traceability in soil surrounding coal gangue areas: combined application of multiple source analysis methods - Ma, Jie; Jiang, Yue; Shen, Zhijie; Zhang, Biaowei; Zhao, Hongjing; Yang, Xiaoxia; Feng, Xue; Sun, Dongyue (Frontiers in Environmental Science, 2025)
In China, coal remains the dominant energy source, leading to substantial production of coal gangue. This study established comparative zones—a study area and a control area—and applied the Geo-Detector model (GDM), Absolute Principal Component Score-Multiple Linear Regression (APCS-MLR) model, and cadmium isotope fingerprinting to delineate the origins of heavy metal(loid)s (HMs) in soil proximate to accumulations of coal gangue. The contents of cadmium (Cd), mercury (Hg), arsenic (As), and lead (Pb) were significantly elevated in the study area relative to the control, whereas the levels of chromium (Cr), copper (Cu), nickel (Ni), and zinc (Zn) displayed no marked differences between the zones, underscoring an intensified pollution level in the study region. The integration of GDM, APCS-MLR, and Cd isotope fingerprinting methods significantly enhanced the precision and dependability in identifying pollution sources. Soil contamination in the study area was predominantly due to persistent coal gangue accumulation, vehicular emissions, and agricultural chemicals, contributing 40.1%, 33.7%, and 26.2% respectively, while in the control area, vehicular emissions and agricultural activities were the main contributors. Surface runoff from coal gangue accumulation emerged as the dominant pathway for soil contamination in the study area. The study underscores the urgency of implementing strategic coal gangue management and mitigation of ecological hazards, particularly those associated with elevated Cd levels.